Artisanal Vegan Soap: Preparation, Physicochemical Characterization and Bacterial Contamination Analysis for Quality Control - Larissa Maculan; Gabriela Tonello; Carlos Henrique Blum da Silva; Marcel Henrique Marcondes Sari; Ana Carla Penteado Feltrin (Brazilian Archives of Biology and Technology)
Abstract Cosmetics made from natural ingredients have gained popularity among a new generation of consumers concerned about their environmental impact. Vegan Soap, in particular, has become a globally important product. This study aimed to produce artisanal vegan bar soap and perform physical-chemical and microbiological analyses to ensure its quality. The quality control study was based on the recommendations in the Quality Control Guide for Cosmetic Products established by ANVISA. Each soap bar weighs 90g and is made from a glycerin base (100% vegetable), lauryl glucoside, cabbage extract (powder), white clay, avocado oil, grape seed oil, and tea green essence. The soap is light green in color and has not undergone any changes in its characteristics. The results of bacterial contamination tests (Staphylococcus aureus and total aerobic mesophilic bacteria) were negative, and there was no evidence of free alkalinity or mechanical stress. Physicochemical analysis revealed a pH of 9.58, a density of 0.98 g/mL, a saponification value of 319.39±4.2% mg of KOH/kg, a peroxide value of 9±1% mEq/kg, and a total fatty acid value of 59.4%±3.2%. These results are within the limits set by standards, indicating that the artisanal vegan soap produced is an acceptable economic and environmental product.